A green separation of Lagenaria siceraria seed oil - Said P.P.; Pradhan R.C.; Rai B.N. (My University, 2025)
Bottle gourd (Lagenaria siceraria) seed oil is found to be an important oil in India as well as in world market due to its medicinal properties. It is used in various cosmetics, skin therapy and in the treatment of benign prostatic hyperplasia. Also some medicines which are formulated using L. siceraria seed oil are used in treatment of treating acne, hyper-seborrhea, alopecia and hirsutism. The aim of this paper was to extract the oil from L. siceraria seed using a green separation process. The effects of pressure, temperature and supercritical fluid's flow rate on the oil yield were investigated using Taguchi experimental design strategy. An orthogonal array, signal-to-noise (S/N) ratio and analysis of variance (ANOVA) were employed to determine significance of various parameters and their interactions. The experimental results showed that pressure and temperature were directly proportional the oil yield. However, the effect of flow rate on the oil yield was not significant. Maximum extraction yield (34.60% (dry basis)) was obtained at 500. bar, 60. °C and flow rate of 15. g/m. © 2013 Elsevier B.V.